VD_FINDINFO HC / 2016 / 370 vom 18. April 2016 - VD Tribunal cantonal (2016)
PROTECTION DE L'UNION CONJUGALE, LOGEMENT DE LA FAMILLE, OBLIGATION D'ENTRETIEN, CONJOINT, TRAIN DE VIE | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 317 al. 2 CPC (CH)